2023
DOI: 10.1108/agjsr-06-2023-0252
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning in healthcare strategic management: a systematic literature review

Sand Mohammad Salhout

Abstract: PurposeThis study specifically seeks to investigate the strategic implementation of machine learning (ML) algorithms and techniques in healthcare institutions to enhance innovation management in healthcare settings.Design/methodology/approach The papers from 2011 to 2021 were considered following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. First, relevant keywords were identified, and screening was performed. Bibliometric analysis was performed. One hundred twenty-three r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Its algorithms can discover sophisticated patterns in these data sets that would be difficult to find using classical statistical methods. In addition, it has many applications, including diagnosis, treatment, and risk prediction [6][7][8] . Systematic literature reviews have identified over 10,000 ML algorithms used in healthcare, with the most common being neural networks, support vector machines, and random forests or decision trees 9 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Its algorithms can discover sophisticated patterns in these data sets that would be difficult to find using classical statistical methods. In addition, it has many applications, including diagnosis, treatment, and risk prediction [6][7][8] . Systematic literature reviews have identified over 10,000 ML algorithms used in healthcare, with the most common being neural networks, support vector machines, and random forests or decision trees 9 .…”
Section: Resultsmentioning
confidence: 99%
“…ML has significantly contributed to health science research by enabling the analysis of complex data sets 3,6,8 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations